OBESITY AND ITS CONSЕQUENCES FOR HEALTH OF CHILDREN, ADOLESCENTS AND ADULTS: WHAT IS KNOWN TODAY? - Beketova, Halyna; Malinovska, Daria; Moshchych, Оstap; Klymova, Yiulia; Beketova, Nataliia; Moshchych, Oleksandr (Eastern Ukrainian Medical Journal, 2025)
Obesity is a common disease with a biological and genetic basis and pronounced psychosocial components. It is diagnosed not only in adults, but also in children and adolescents with the subsequent formation of severe comorbid socially significant pathology and complications, impaired quality of life and reduced life expectancy. Obesity is recognized as a non-communicable epidemic of the 21st century, a global medical and psychosocial problem, and a heavy economic burden on the healthcare system of countries with any level of material prosperity, which requires further study and effective solutions. The purpose of the study is to conduct a narrative review of the scientific literature to clarify the problematic aspects of obesity in children and adolescents in modern conditions. Methods. The literature review was based on published scientific studies using the information search systems PubMed, Web of Science, Scopus, Google Scholar, and ResearchGate. We considered studies published mainly in the last 5 years. 124 scientific publications were selected for this article. Results. The review highlights issues related to modern approaches of verifying overweight and obesity in childhood, types of adipose tissue, and their biological functions in the body. It was found that in the recent decades, risk factors for obesity in children of different age groups have been actively studied, however, the scientific literature lacks data on determining their statistically significant combinations necessary for creating appropriate mathematical prediction models. The paper provides current data on the pathophysiological mechanisms of obesity formation in children and adolescents (the role of genetic factors; microbiome disorders using the latest genetic sequencing methods and all components of the microbiome-immune-metabolic axis; stress and psycho-emotional changes; unhealthy lifestyle; exposure to glutamate-containing foods, vitamin D insufficiency/deficiency). The results of clinical and experimental studies on the influence of obesity on the formation of such socially significant diseases as atherogenic dyslipidemia, arterial hypertension, hyperglycemia and non-insulin-dependent diabetes mellitus, metabolic syndrome, bronchial asthma, gallstone disease and metabolically associated steatotic liver disease, musculoskeletal problems, polycystic ovary syndrome and obstructive sleep apnea. The impact of glutamate-induced (alimentary) obesity on the development of gastroesophageal reflux disease, erosive reflux esophagitis, and Barrett's esophagus in adolescents is reviewed. Conclusion. Insufficiently analysed aspects of the growing obesity crisis require further studying of the problem in children and adolescents in order to create a modern algorithm for predicting risks of the disease development and effectively manage such patients by specialists of a multidisciplinary team as well as to prevent the disease progression and the formation of life-threatening complications and early death.